(untitled) (Journal of Pathology of Nepal, 2023)
Background: Esthesioneuroblastoma is a slow-growing rare malignant neuroectodermal tumor arising from the olfactory epithelium. It has a bimodal incidence with peaks in the second and third decades of life and the sixth and seventh decades of life with equal incidence among men and women. Prognostic factors include the Hyams grade and modified Kadish stage. This study analyzed the clinicopathological features of esthesioneuroblastoma. Materials and methods- Retrospective study of patients who were diagnosed with esthesioneuroblastoma at a tertiary care hospital between January 2012 and May 2019 was conducted. The research was performed according to the World Medical Association Declaration of Helsinki. Institutional research committee approval (IEC: 473/2019) was obtained. Results: Clinicopathological profiles of 8 patients who were diagnosed with esthesioneuroblastoma during the period were included. Among the eight patients, five were female and three were male. Common presenting complaints were nasal obstruction, difficulty in breathing, epistaxis, local pain, and anosmia. The average age of presentation was 52 years, ranging from 14 to 73 years. Anterior rhinoscopic examination in these cases showed a polypoid mass located in the nasal cavity. According to the Hyams grading system, three of the eight cases were grade-2 and the remaining five cases were grade-3 Hyams histological grade. Three cases exhibited foci of ganglioneuroblastic transformation. Three patients had metastases to cervical lymph nodes and three patients had recurrence. Conclusions: Esthesioneuroblastoma is a rare aggressive malignant tumor. It can exhibit divergent epithelial or ganglionic differentiation. A proper diagnosis should be made, graded and staged before proceeding to treatment.